2009
DOI: 10.1097/jsm.0b013e318193428f
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a 10-Week Multidisciplinary Tai Chi Intervention in Sedentary Obese Women

Abstract: The observed benefits over a 30-week period of a multidisciplinary weight management program incorporating TC exercises on physical functioning mood and dietary restraint need further understanding of how sedentary obese women adhere to physical activity like TC or other alternative exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 11 publications
2
55
0
Order By: Relevance
“…The observed enhancement of GSE through Taiji practice is in accordance with prior research [39][40][41]. Considering all four sources of self-efficacy, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed enhancement of GSE through Taiji practice is in accordance with prior research [39][40][41]. Considering all four sources of self-efficacy, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Positive effects of Taiji on domain-specific self-efficacy have been repeatedly observed, namely on self-efficacy related to exercise behaviour [19,[32][33][34][35], pain management [36], physical 4 capability [37] and fall prevention [34,38]. A significant increase in GSE following Taiji has been reported in three randomised controlled trials [39][40][41]. The notion that GSE is likely to mediate stress reducing treatment effects is supported by the cognitive transactional stress theory [42]; [43].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable findings were recently reported in sedentary women. 36 In contrast, independent of the group considered, blood pressure was significantly lower after the tai chi intervention program, which is in accordance with Young et al, 37 who noted similar results after a 12-week tai chi intervention in adults 60 years or older. Because FM, BMI, 38 and blood pressure 39 are widely associated with increased risks of CVD, tai chi may be considered as an appropriate activity to prevent or lower the occurrence of CVD in dynapenic postmenopausal women, as previously stated by Lee et al 16 However, in contrast to the findings of Lan et al 40 and Audette et al, 18 our intervention had no positive effect on cardiorespiratory functions.…”
Section: Discussionsupporting
confidence: 84%
“…Among the 50 studies in Table 1, no serious AEs related to Tai Chi was reported, and 32 studies 18, 20, 21, 26-29, 31-34, 36-39, 41-44, 50-52, 55-57, 59-65 reported no occurrence of any AEs related to intervention. Fifteen 16, 17, 19, 23-25, 30, 45, 47-49, 53, 54, 58, 59 of the 50 studies specifically reported occurrences of minor musculoskeletal aches and pain, with complaints of lower extremity pain (knee and ankle) being most common.…”
Section: Resultsmentioning
confidence: 99%